2017
DOI: 10.1177/0003489417729834
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Adenotonsillectomy and Risk of Velopharyngeal Insufficiency in Children With Prader-Willi Syndrome

Abstract: This study demonstrated a higher rate of VPI after T&A in PW children as compared to another at-risk cohort, T21 patients. While the OAHI decreased after T&A in both groups, a significant number of children with PW or T21 had persistent OSA. Further investigation into the optimal management of OSA, while preventing treatment complications such as VPI, is needed for children with these high-risk conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Only one patient had an adenotonsillectomy between the first and second polygraph, her AHI worsening from 1.5 to 11.5 after surgery. This finding suggests that adenotonsillectomy may be less successful in SRS patients than in the general population, as already reported for PWS patients (29)(30)(31). Furthermore, an ENT intervention concerning tonsils in SRS patients can result in a voice change and worsen a preexisting high-pitched voice, quite common in these patients.…”
Section: Discussionsupporting
confidence: 51%
“…Only one patient had an adenotonsillectomy between the first and second polygraph, her AHI worsening from 1.5 to 11.5 after surgery. This finding suggests that adenotonsillectomy may be less successful in SRS patients than in the general population, as already reported for PWS patients (29)(30)(31). Furthermore, an ENT intervention concerning tonsils in SRS patients can result in a voice change and worsen a preexisting high-pitched voice, quite common in these patients.…”
Section: Discussionsupporting
confidence: 51%
“…A systematic review showed that A&T was effective in reducing OSA for some PWS children, but alternative treatments may be considered, given the only moderate response rate (59). OAHI decreased after A&T in 22 children, but a significant number had persistent OSA (79). Velopharyngeal dysfunctions (VPD) may occur after A&T (80).…”
Section: Prader-willi Syndromementioning
confidence: 99%
“…Hypotonia, facial dysmorphic features, obesity, and adenotonsillar hypertrophy may be the possible causes of OSA in children with PWS. 10,16,17,43,49,52…”
Section: Discussionmentioning
confidence: 99%
“…All 6 studies reported the data for AHI changes postoperatively. 43,44,[46][47][48][49] The AHI results were 13.1 events/h (95% CI, 11.0-15.1) before surgery and 4.6 events/h (95% CI, 4.1-5.1) after surgery. Overall, the mean change in postoperative AHI was a reduction of 8.0 events/ h (95% CI, 210.8 to 25.1; Figure 2) and was statistically significant.…”
Section: Outcomes Of Surgery In Children With Pwsmentioning
confidence: 99%
See 1 more Smart Citation